2020
DOI: 10.1021/acs.jpcc.9b11116
|View full text |Cite
|
Sign up to set email alerts
|

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures

Abstract: The rapid and reliable detection of lethal agents such as sarin is of increasing importance. Here, density-functional theory (DFT) is used to compare the interaction of sarin with single-metal-centered phthalocyanine (MPc) and MPc layer structures to a benign model system, i.e., the adsorption of dimethyl methylphosphonate (DMMP). The calculations show that sarin and DMMP behave nearly identical to the various MPcs studied. Among NiPc, CuPc, CoPc, and zinc phthalocyanine (ZnPc), we find the interaction of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Then, the total NEXAFS spectrum of the molecular system was obtained from the superposition of the individual spectra offset by the corresponding core-level shifts, calculated within DFT for each carbon atom (see, e.g. , refs , , , and for further details). For structures with axial symmetry, the XAS cross section (σ XAS ) for an E -field component, tilted by an angle θ with respect to the surface normal, can be accurately calculated by averaging over two orthogonal azimuthal orientations (for an arbitrary angle φ 0 ): In the present case, the 3-fold symmetry of the substrate is broken by the attached molecules.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Then, the total NEXAFS spectrum of the molecular system was obtained from the superposition of the individual spectra offset by the corresponding core-level shifts, calculated within DFT for each carbon atom (see, e.g. , refs , , , and for further details). For structures with axial symmetry, the XAS cross section (σ XAS ) for an E -field component, tilted by an angle θ with respect to the surface normal, can be accurately calculated by averaging over two orthogonal azimuthal orientations (for an arbitrary angle φ 0 ): In the present case, the 3-fold symmetry of the substrate is broken by the attached molecules.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…They found that gas adsorption causes the electronic structure on the surface and local spin density polarization to change drastically. The above studies indicate that the process of gas adsorption is related to the crystal structure and electronic characteristics of the surface, as well as the electronic structure and molecular orbitals of the adsorbed gas …”
mentioning
confidence: 97%
“…The above studies indicate that the process of gas adsorption is related to the crystal structure and electronic characteristics of the surface, as well as the electronic structure and molecular orbitals of the adsorbed gas. 40 We used first-principles calculations to clarify the changes in the electronic structure and the periodicity of the lattice on WO 3 following gas adsorption. In particular, the charge transfer 39 mechanism was investigated using Bader charge analysis.…”
mentioning
confidence: 99%
“…This principle can be straightforwardly extrapolated for the entire class of strong electron–donor/acceptor toxic analyte molecules like NO 2 , NO, CO 2 , CO, NH 3, and more, and even for lethal agents as dimethyl methylphosphonate (DMMP) and sarin. [ 57 ] We scrutinized light absorption mechanisms in the hybrid AuNP–CT monolayer and found out the sixfold increase in efficiency of the internal optical transition from nondegenerate low‐lying doubly occupied orbitals toward degenerate half‐empty orbital that can be exploited for ultrafast control over the SOMO–LUMO transition and possibly for switching an electronic configuration of SOMO via breaking its degeneracy. As there is only one electron at SOMO, a paramagnetic response from CT complexes can be anticipated.…”
Section: Discussionmentioning
confidence: 99%